Marketing Communications / An Integrated Approach 4th Edition - Smith P R (Paul Russell); Taylor Jonathan (Kogan Page Limited, 2004)
A comprehensive framework for understanding the individual contribution and the collective combination of all the communication tools. Foreword, Acknowledgements, The Background to the Communications Process, The Marketing Communication Tools, Index.